Childhood trauma among adult patients with mental illness in south-western Uganda: A hospital-based study - Vivalya, Bives Mutume Nzanzu; Akimana, Benedict; Ashaba, Scholastic (SSM-Mental Health, 2023)
Introduction: Childhood trauma plays a central role in the long-term outcomes and quality of life of adults with mental disorders. Its burden among patients receiving mental health care in rural health facilities has not been established formally. This study determined the prevalence of childhood trauma among individuals receiving treatment at two mental health facilities in southwestern Uganda. Methods: Two hundred forty-nine adult psychiatric patients were screened for childhood trauma using the Adverse Childhood Experience International Questionnaire. Descriptive analyses were performed to determine the information on prevalence rates, cumulative traumas and types of trauma experienced by individuals receiving treatment at Ugandan mental health facilities. Results: Nine in ten mentally ill patients had experienced childhood adversities which were more significant greater among participants diagnosed with depression and substance use disorder compared to those with bipolar disorder and schizophrenia. 99.6% of participants with childhood trauma experienced multiple forms of adverse childhood adversities. The commonest adverse childhood experiences in our sample were witnessing violence against household members, physical neglect, bullying and emotional violence. Conclusion: Our results highlight the extremely high rate of childhood trauma among patients with mental disorders and raise the global health policy issue revealing the need for a primary health level intervention to address its effects along the mainstream mental health care.
Keywords: Childhood trauma; Mental disorders; Uganda